2009
DOI: 10.1128/jvi.00683-09
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacovirological Impact of an Integrase Inhibitor on Human Immunodeficiency Virus Type 1 cDNA Species In Vivo

Abstract: Clinical trials of the first approved integrase inhibitor (INI), raltegravir, have demonstrated a drop in the human immunodeficiency virus type 1 (HIV-1) RNA loads of infected patients that was unexpectedly more rapid than that with a potent reverse transcriptase inhibitor, and apparently dose independent. These clinical outcomes are not understood. In tissue culture, although their inhibition of integration is well documented, the effects of INIs on levels of unintegrated HIV-1 cDNAs have been variable. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…RAL is a new drug belonging to a new class of antiretrovirals (INIs), which has demonstrated an exquisite potency, a clean safety profile also at once-daily dosing of 800 mg/day, and to not accumulate in PBMCs, with intracellular concentrations being about 1/10 of the concentrations in plasma (Goffinet et al, 2009;Moltó et al, 2011;Murray et al, 2007;Steigbigel et al, 2008;Summa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RAL is a new drug belonging to a new class of antiretrovirals (INIs), which has demonstrated an exquisite potency, a clean safety profile also at once-daily dosing of 800 mg/day, and to not accumulate in PBMCs, with intracellular concentrations being about 1/10 of the concentrations in plasma (Goffinet et al, 2009;Moltó et al, 2011;Murray et al, 2007;Steigbigel et al, 2008;Summa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one of the most exciting recent advances in HIV-1 pharmacotherapy has been the approval in the October 2007 by Food and Drug Administration (FDA) of the first INI, the new pyrimidone carboxamide raltegravir (RAL) provided with a high potency and generally well tolerability (Cocohoba and Dong, 2008;Goffinet et al, 2009;Moltò et al, 2011;Steigbigel et al, 2008;Summa et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…This is in contrast to the parameter choices concerning cells latently infected preintegration used previously (26), which are in conflict with the known properties of this viral reservoir. Others have suggested that the greater decay observed with RAL could be a result of the gene expression from or the apoptosis triggered by unintegrated DNA that accumulates following the use of an IN inhibitor (15). However, these effects would occur in cells that are unable to produce virus (since productive infection has been blocked by the IN inhibitor) and therefore would not be expected to contribute to the viral load, although the possibility that these effects play a role in superinfected cells cannot be excluded.…”
mentioning
confidence: 99%
“…They include differences in the time until drug bioavailability, differences in drug potency, a role for cells latently infected preintegration, the greater penetration of certain drugs into sanctuary sites, the stage of viral replication targeted, and the IN inhibitor-induced accumulation of unintegrated viral DNA (15,23,26,33,34). On the basis of the mathematical modeling of viral load decay, it has been proposed that the clinical observations can be explained by the effect of RAL on cells latently infected preintegration (26).…”
mentioning
confidence: 99%
“…Our parallel efforts in the rat species have markedly increased in vivo susceptibility to systemic HIV-1 challenge. The human-CD4 (hCD4)/hCCR5-transgenic rat model has facilitated preclinical evaluation of antiviral drugs targeting entry, reverse transcriptase, and integrase (29,30) and has contributed to aspects of viral pathogenesis (53,59) and testing of a vaccine candidate (14). Despite a high proviral load in lymphatic organs, the current transgenic rat model still has limitations, including low and transient viremia and lack of HIV disease.…”
mentioning
confidence: 99%